(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
This article analyzes the national liberation struggle of the kazakh people against the Russian Empire on the example of the kazakh khan-chingizid Kenesary Kasymov. A historiographical review of the authors who studied the personality of Kenesary is given, situations revealing the character, patriotism, and personal qualities of the Kazakh Khan Kenesary are analyzed. The causes and consequences of the national liberation struggle of the Kazakh people against the Russian Empire are considered. And also some aspects of the life and work of Khan Kenesary Kasymov are revealed.